Multidimensional vulnerability and financial risk protection in health in contexts of protracted conflict: Evidence from the Occupied Palestinian Territory - Julia Hatamyar; Sally Shayeb; Akseer Hussain; Weeam Hammoudeh; Sumit Mazumdar; Rodrigo Moreno-Serra (PLoS ONE, 2025)
This paper proposes a multidimensional vulnerability index for a setting of protracted conflict, which is applied to study the relationship between financial vulnerability and catastrophic healthcare expenditure (CHE) incidence in the Occupied Palestinian Territory in 2018. We find that our index better captures the extent of financial risk protection in health compared to conventional measures of financial welfare. Results indicate that the most vulnerable groups experience a significantly higher likelihood of incurring CHE, and this likelihood is increased for those living in the West Bank compared to the Gaza Strip. We also find a lack of protection from existing health insurance types against the risk of CHE. Our analysis provides valuable insights about key aspects, such as health financing and insurance bottlenecks, that will deserve careful policy attention in efforts to rebuild the Palestinian health system, following the Israel-Hamas war.